Two new species of Tenuipalpus Donnadieu, 1875 (Acari: Trombidiformes: Tenuipalpidae) from Iran - Safdarkhani, Hamid Khadem; Asadi, Mahdieh; Seeman, Owen D. (Zootaxa, 2018)
Two new flat mite species (Acari: Trombidiformes: Tenuipalpidae), Tenuipalpus iranicus sp. nov. ex. Salix aegyptiaca (Salicaceae) and Tenuipalpus kermanicus sp. nov. ex. Tamarix aphylla (Tamaricaceae) from the Hormozgan and Kerman provinces of Iran, respectively, are described and illustrated. These species belong to the proteae species group. Tenuipalpus iranicus sp. nov. is placed in the xerocolus subgroup due to having two pairs each of setae 3a and 4a, and T. kermanicus sp. nov. is placed in the keiensis subgroup because it has one pair of setae 3a and two pairs of 4a.